Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Answer:
- 84
Step-by-step explanation:
Average rate of change between x = 2 and x = 4 is:
- [f(4) - f(2)]/(4 - 2) =
- (3*4³ - 1 - 3*2³ + 1)/2 =
- 168/2 =
- 84
[tex]\boxed{\sf Average\: change=\dfrac{f(a)-f(b)}{a-b}}[/tex]
[tex]\\ \sf\longmapsto f(x)=3x^3-1[/tex]
[tex]\\ \sf\longmapsto f(4)=3(4)^3-1=3(64)-1=192-1=191[/tex]
[tex]\\ \sf\longmapsto f(2)=3(2)^3-1=3(8)-1=24-1=23[/tex]
Average change
[tex]\\ \sf\longmapsto \dfrac{192-23}{4-2}[/tex]
[tex]\\ \sf\longmapsto \dfrac{168}{2}[/tex]
[tex]\\ \sf\longmapsto 84[/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.